2008
DOI: 10.1002/iub.102
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin and thioredoxin binding protein 2 in the liver

Abstract: SummaryThioredoxin (TRX) is a 12-kDa protein with redox-active dithiol in the active site -Cys-Gly-Pro-Cys-and constitutes a major thiol reducing system. TRX protects cells from stressinduced damage through antioxidative, antiapoptotic, and antiinflammatory effect. In animal models, thioacetamide (TAA)-induced acute hepatitis and TAA-induced liver fibrosis was attenuated in TRX transgenic (TRXTG) mice. Plasma level of TRX is a good marker for hepatitis and nonalcoholic steatohepatitis (NASH) in human patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This is especially intriguing for mouse serum, in which the Trx1 levels are extremely low (1–10 nM) [2]. Although Trx1 is secreted as full-length and truncated forms [19,20], we only detected the full-length form, suggesting that the truncated Trx1 form is either much less abundant or it is not trapped by the TR1 column. A 55 kDa band was also observed in the rat brain sample that corresponds to TR1 (see above).…”
Section: Resultsmentioning
confidence: 92%
“…This is especially intriguing for mouse serum, in which the Trx1 levels are extremely low (1–10 nM) [2]. Although Trx1 is secreted as full-length and truncated forms [19,20], we only detected the full-length form, suggesting that the truncated Trx1 form is either much less abundant or it is not trapped by the TR1 column. A 55 kDa band was also observed in the rat brain sample that corresponds to TR1 (see above).…”
Section: Resultsmentioning
confidence: 92%
“…In the present study, a rat model of TAA-induced liver fibrosis and cirrhosis was 64 used to identify urinary protein biomarkers related to the developmental process (1 week, supernatant was removed, the pellets were re-suspended with lysis buffer (8 M urea, 2 M 120 thiourea, 25 mM dithiothreitol (DTT) and 50 mM Tris) [36] . Protein concentrations were 121 measured using the Bradford method.…”
mentioning
confidence: 99%
“…Carbonic anhydrase 3 is also a 345 biomarker of liver injury [62] . Thioredoxin has a potential to attenuate liver fibrosis via 346 suppressing oxidative stress and inhibiting proliferation of stellate cells [63] and plays 347 important roles in the pathophysiology of liver diseases [64] . Overexpression of 348 thioredoxin has been reported to prevent TAA-induced hepatic fibrosis in mice [63] .…”
mentioning
confidence: 99%
“…14 Since Trx is a redox-sensitive molecule, 15 serum Trx levels are believed to be a clinically useful marker for oxidative stress, and the ratio of expression of Trx and Trx binding protein 2, which is an endogenous inhibitor of Trx, could be a novel marker of liver diseases like NASH. 16 Sumida et al, 17 and Nakashima et al 18 reported that serum Trx concentrations were obviously elevated in patients with NASH compared with the concentrations in patients with simple steatosis or in healthy volunteers. Mitsuyoshi et al 6 reported that the levels of Trx genes were significantly higher in NAFLD patients than in a control group and tended to increase as the stage progressed.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic Trx expression may exert a therapeutic effect by conferring resistance to various types of stress and cell death, which may be applied in future bio‐artificial liver support systems and gene therapy for liver diseases 14 . Since Trx is a redox‐sensitive molecule, 15 serum Trx levels are believed to be a clinically useful marker for oxidative stress, and the ratio of expression of Trx and Trx binding protein 2, which is an endogenous inhibitor of Trx, could be a novel marker of liver diseases like NASH 16 . Sumida et al., 17 and Nakashima et al.…”
Section: Discussionmentioning
confidence: 99%